2017
DOI: 10.1371/journal.pone.0175265
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of genes conferring desirable agronomic traits from Agropyron cristatum chromosome 1P

Abstract: Agropyron cristatum (L.) Gaertn. (2n = 4x = 28, PPPP), a wild relative of common wheat, possesses many potentially valuable genes for wheat breeding. To transfer these genes into wheat, a series of wheat-A. cristatum derivatives have been obtained in our laboratory. In this study, a wheat-A. cristatum derivative II-3-1 was obtained, which was proven to contain a 1P (1A) disomic substitution and 2P disomic addition line with 40 wheat chromosomes and two pairs of A. cristatum chromosomes by genomic in situ hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Wheat– A. cristatum alien addition/substitution lines were obtained from several generations of backcrossing or selfing following the hybridization of the common wheat Fukuho with A. cristatum accession ‘Z559’ (2 n = 4 x = 28, PPPP) (Table ). Among these lines, II‐3‐1, II‐9‐1, II‐8‐1, II‐7‐1, II‐21‐2, II‐21‐6, 5113‐2, 5114‐3, 4844‐12, 4844‐8, 5038, 5043, II‐5‐1 and II‐26‐1 were identified previously (Han et al ., ; Pan et al ., ; Wu et al ., ). ‘Z1842’, ‘Z2098’ and their 119 progeny, Fukuho, ‘Z559’ and addition/substitution lines were planted in the glasshouse at the Chinese Academy of Agricultural Sciences, Beijing, China.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Wheat– A. cristatum alien addition/substitution lines were obtained from several generations of backcrossing or selfing following the hybridization of the common wheat Fukuho with A. cristatum accession ‘Z559’ (2 n = 4 x = 28, PPPP) (Table ). Among these lines, II‐3‐1, II‐9‐1, II‐8‐1, II‐7‐1, II‐21‐2, II‐21‐6, 5113‐2, 5114‐3, 4844‐12, 4844‐8, 5038, 5043, II‐5‐1 and II‐26‐1 were identified previously (Han et al ., ; Pan et al ., ; Wu et al ., ). ‘Z1842’, ‘Z2098’ and their 119 progeny, Fukuho, ‘Z559’ and addition/substitution lines were planted in the glasshouse at the Chinese Academy of Agricultural Sciences, Beijing, China.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In particular, An et al [31] obtained a new wheat-rye addition line called WR35 via crossing Xiaoyan 6 with the rye cultivar German White, where the addition line exhibited resistance to powdery mildew and stripe rust, and a high kernel number per spike. Pan et al [32] also found that the 1P chromosome from Agropyron cristatum enhanced the spike length and tiller number in wheat, and a wheat-A. cristatum 1P addition line was obtained using molecular and phenotypic identification techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows for the genome-specific chromosome labeling in the cells of allopolyploid or hybrid species. It has been widely used in plant studies to identify putative parental genomes in the interspecific or intergeneric hybrids or allopolyploids (for the review see Chester et al 2010;Silva and Souza, 2013), to study the evolution of polyploid genomes (Song et al 1995;Gaeta et al 2007;Majka et al 2018;Tan et al 2017), or to detect the introgression of alien chromatin (Schneider et al 2005;Tan et al 2005) Manuscript to be reviewed as translocation (Kruppa et al 2013), addition (Molnar-Lang et al 2000;Ji and Chetelat 2007), or substitution (Pan et al 2017) lines.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%